Decoding Trauma, Identity, and Resilience to Caste-based Oppression in Premanand Gajvee’s Kirwant - Aditi Gaur; Prabha Lama (Emerging Trends in Languages, 2024)
Dalit literature, deeply rooted in political reform and personal confession, often explores societal and individual challenges stemming from the Ambedkarite movement's rebellion and efforts. Premanand Gajvee, a celebrated Marathi playwright and poet, a seminal figure in Dalit literature, is celebrated for his contributions to the Dalit Theatre of Protest. His play Kirwant, inspired by the real-life issues of lower-caste Marathi Hindu Brahmins, critiques societal flaws. This study focuses on the themes of trauma, resistance and identity in Kirwant, examining the opposing reactions of two characters, Vasudeo and Siddheshwar, to caste-based oppression. Vasudeo's strong self-identity fuels his resistance, manifesting in anger and violence, while Siddheshwar's vulnerable social position and psychological trauma underscores his submission. The study explores the dualities in their responses, namely how trauma and identity performance influence their actions. By looking into the nuances of resilience and submission in Kirwant this study aims to gain a better understanding of the complexities of the marginalized experiences and their responses to systematic oppression. It focuses on how identity is constantly created and performed in response to societal pressures, providing insights into how marginalized people navigate and fight dominant power structures. The goal of the study is to advance a more sophisticated comprehension of trauma, identity, and resistance in Dalit writing.
Keywords: Dalit literature; Resistance; identity; kirwant; marathi theatre; trauma